Covalent conjugation of whey protein isolate hydrolysates and galactose through Maillard reaction to improve the functional properties and antioxidant activity. (March 2020) - Zhang, Xiuxiu; Li, Xiaodong; Liu, Lu; Wang, Lina; Massounga Bora, Awa Fanny; Du, Lingling
Abstract: Galactose was grafted onto whey protein isolate (WPI) and whey protein hydrolysates (WPHs) via the Maillard reaction (95 °C, 0–4 h). The pH, browning intensity, structure, functional properties and antioxidant activity of conjugates were evaluated. The pH, browning and degree of conjugation were at maximum after heating for 4 h. The Maillard reaction changed the WPI and WPHs to a looser secondary structure. Conjugates of WPI and WPHs with galactose had higher water holding capacity, foaming capacity and stability, and antioxidant activity. Compared with the WPI-Galactose conjugates, WPH-Galactose conjugates showed better functional properties and higher antioxidant activity, and its highest reducing power was 0.923; ABTS + radical scavenging ability was 69.81%; hydroxyl radical scavenging ability was 89.05%. These findings indicate that the covalent conjugation of WPH-Galactose conjugates can be used as a potential ingredient and a novel wall material to encapsulate bioactive compounds.